2008
DOI: 10.1007/s10641-008-9342-x
|View full text |Cite
|
Sign up to set email alerts
|

Age composition, growth, and reproductive biology of yellow catfish (Peltobagrus fulvidraco, Bagridae) in Ce Lake of Hubei Province, Central China

Abstract: This study presents fundamental information on the reproductive biology, size and age composition, and growth of yellow catfish, Peltobagrus fulvidraco. Sampling was carried out monthly from Ce

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…We estimate that yellow catfish spawning occurs from April to June throughout Three Gorges Reservoir. Similar to this study, yellow catfish from Lake Ce (Yangtze River Basin, China) were also found to spawn from May to August, with peak GSI occurring during June and July (Cao et al., ). In Lake Liangzi (Yangtze River Basin, China), reproduction was again found to occur from May to late July (Cao et al., ).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…We estimate that yellow catfish spawning occurs from April to June throughout Three Gorges Reservoir. Similar to this study, yellow catfish from Lake Ce (Yangtze River Basin, China) were also found to spawn from May to August, with peak GSI occurring during June and July (Cao et al., ). In Lake Liangzi (Yangtze River Basin, China), reproduction was again found to occur from May to late July (Cao et al., ).…”
Section: Discussionsupporting
confidence: 79%
“…Cao et al. () also reported a relatively low absolute fecundity for yellow catfish ranging from 657 to 11 696, and other studies reported similar fecundity numbers in Honghu Lake and Poyang Lake, China (794 to ~4873 and 1132 to ~12 412, respectively (Cao et al., ). We recommend that harvesting or fishing effort should likely be managed to target the non‐reproductive seasons of yellow catfish in Three Gorges Reservoir so as to conserve vulnerable spawning stocks.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Most mature miRNA sequences are conserved across amphibians, fish, and mammals (Kloosterman & Plasterk, ). Recently, miRNA expression has also been examined in the gonads of fish and mammals, such as allotetraploid hybrid fish and Carassius auratus (Zhou et al, ), P. fulvidraco (Cao et al, ), O. niloticus (Xiao et al, ), P. olivaceus (Lee et al, ), primates (Yan et al, ), and mice (Reid et al, ), using next‐generation sequencing technologies. These studies show that miRNAs are very important for sex differentiation and gonadal development.…”
Section: Introductionmentioning
confidence: 99%